Effect of different chemical treatments on the rice straw stored dried or soaked - Santos, Geraldo T. dos; Prates, Ênio R. (Pesquisa Agropecuaria Brasileira, 2014)
The effect of four different chemical treatments (NaCl, NaOH, KOH and Ca (OH)2), at three levels zero, four and 8% of dry matter (DM) was studied on the chemical composition and in vitro organic matter digestibility (IVOMD) of rice straw, submitted to two different forms of preservation: dry and soaked. Both experiments were analysed by a completely randomized design. The chemical treatments proved to have an inconsistent effect on the chemical composition of rice straw. Both forms of conservation had identical effects on the in vitro organic matter digestibility, but the treatment with NaCl did not affect (P > 0,05) the IVOMD of rice straw. On the other hand, the alkalis tested in both experiments were effective (P < 0,05) in improving the IVOMD, with NaOH being the most effective.